Carbon nanotubes filled with a chemotherapeutic agent: a nanocarrier mediates inhibition of tumor cell growth. (April 2008) - Hampel, Silke; Kunze, Doreen; Haase, Diana; Kräämer, Kai; Rauschenbach, Mandy; Ritschel, Manfred; Leonhardt, Albrecht; Thomas, Jüürgen; Oswald, Steffen; Hoffmann, Volker; Büüchner, Bernd
Aim: In this paper, carbon nanotubes (CNTs) are presented as feasible carriers for carboplatin, a therapeutic agent for cancer treatment. The drug was introduced into CNTs to demonstrate that they are suited as nanocontainers and nanocarriers and can release the drug to initialize its medical virtue.Method: The filling was accomplished by a wet-chemical approach after the CNTs were opened. The effect on cell proliferation and cytotoxicity of the carboplatin-filled CNT was investigated by using a viability assays.Results: Using different analysis methods such as electron energy loss spectroscopy and x-ray photoelectron spectroscopy the structure of carboplatin incorporated into the CNTs was found to be retained. In vitro studies showed that carboplatin-filled CNTs inhibited growth of bladder cancer cells whereas unfilled, opened CNTs barely affected cancer cell growth.Conclusion: A reversible filling––emptying process could be performed successfully within this work. This highlights the potential of CNTs for applications in the field of drug delivery.